ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION WITH ATTITUDE TOWARD PRODUCT USED AND BRAND IMAGE AS MEDIATION VARIABLES - Amirah, Ghassani Ghina; Andriyansah, Andriyansah; Edy Herman, Lalu (CV. Era Digital Nusantara, 2024)
This study aims to determine the role of electronic word-of-mouth on Purchase Intention mediated Attitude toward Product Used and Brand Image. The sample used is the consumer of Proargi-9+ Products from Synergy WorldWide Indonesia. The technique is proportional sample by using SEM, SmartPLS. The results of the research are: Electronic word of has positive and significant effect on attitudes toward product used which answer the research objectives and the first hypothesis. Electronic word of mouth has a positive and significant effect on Brand Image which answer the research objectives and the second hypothesis. Electronic word of mouth has significant positive effect on purchase intention which answer the third hypothesis. Attitude toward product used has a positive effect on Brand Image, which answer the fourth hypothesis. Attitude toward product used has a positive and significant effect on purchase intention, which answer the fifth hypothesis. Brand Image has positive but not significant effect on Purchase Intention, which answer the sixth hypothesis. Attitude toward product used directly mediates the relationship between electronic word of mouth and purchase intention, which answer the seventh hypothesis. Brand image directly mediates the relationship between electronic word of mouth and purchase intention, which answers the eighth hypothesis.